Response of rice genotypes with differential nitrate reductase-dependent NO synthesis to melatonin under ZnO nanoparticles' (NPs) stress. (July 2020) - Huang, Zhuoli; Xie, Wenjun; Wang, Meng; Liu, Xuwei; Ashraf, Umair; Qin, Dejun; Zhuang, Maosen; Li, Wu; Li, Yuzhan; Wang, Shuli; Tian, Hua; Mo, Zhaowen
Abstract: Nitrate reductase is a nitric oxide (NO) induced enzyme in plants, NO acts as a signaling molecule under ZnO NPs-induced stress whereas melatonin (N-acetyl-5-methoxytryptamine) could improve morpho-physiological attributes of plants under adverse conditions. In present study, seedlings of two rice genotypes differed regarding nitrate reductase activities i.e., transgenic 'NR' and wild type 'WT' were applied with two melatonin levels i.e., 0, 10 μΜ regarded as M0, M10, respectively and three levels of ZnO NPs i.e., 0, 50, 500 mg L −1 regarded as ZnO NPs0, ZnO NPs50 and ZnO NPs500, respectively. Results revealed that melatonin application substantially increased the dry biomass accumulation of both rice genotypes under all ZnO NPs levels. The root growth, mineral absorption as well as the antioxidant responses were also improved by melatonin application under ZnO NPs stress. The interactive effects of melatonin and genotype on plant growth, antioxidant responses and mineral contents i.e., Zn, Na, Fe and Mn were also found significant under different ZnO NPs stress. Furthermore, total plant dry weight was significantly correlated with the leaf dry weight, root volume, catalase (CAT) activity in leaves, Na accumulation in stem sheath and Fe accumulation in root under both M0 and M10 treatments. Moreover, the comparative transcriptome analysis identified key genes which were responsible for melatonin and NO-induced modulations in plant growth under ZnO NPs stress. Overall, melatonin could improve the morphological growth of the rice plants by modulating root-shoot characteristics, antioxidant activities and mineral uptake in root and shoot of rice. Highlights: Melatonin could significantly increase dry biomass accumulation rice across three ZnO NPs. Melatonin improved the root growth parameters, mineral absorption and the antioxidant responses. Melatonin and genotype had interactive effect on morphology and biochemistry under ZnO NPs stress. The comparative transcriptome analysis identified key genes.